Childhood Obesity: Still a Major Concern - Parasuraman, Subramani; Krishnamoorthy, Venkateskumar (Free Radicals and Antioxidants)
Overweight and obesity are defined as “abnormal or excessive fat accumulation that presents a risk to health”.1 The prevalence of obesity is increasing every year and has nearly tripled since 1975. More than 19 billon adults in 2016 and about 89 million children under the age 5 years are obese in 2020.2 World Obesity Federation estimates suggest that about 250 million children ageing between 5 and 19 years old will be obese by 2030. Reports also predict that the population of obese children (5 and 19 years) are expected to rise to 62 million in China, 27 million in India, 17 million in the USA, 1.8 million in Malaysia, 1.3 million in the UK and 0.08 million in Singapore by 2030.3 The complete data on ‘Childhood Obesity’ is available in ‘Atlas of Childhood Obesity [2019 edition]’ published by the World Obesity Federation, London. Again, the COVID-19 pandemic had significantly affected children’s daily lives, reduced their physical activity, increased their stress levels and had contributed to such a high incidence of childhood obesity.4,5 Woolford et al., assessed the changes in body-mass index (increased) among children during COVID- 19 restrictions and reported an increase in pediatric obesity during the aforesaid period.6